Animal continuities. Arguments against human/non-human animal dichotomy - Vernal, Javier Ignacio (2011)
At present, there is still a deep need to differentiate the members of the species Homo sapiens from the individuals belonging to the rest of the animal kingdom. As a consequence of this need arises the dichotomy human/non-human animal based on artificial and groundless differences that leads to actions always harmful to the non-human animals. In this work we want to show, on the one hand, that many of the characteristics proposed as specifically human are shared by at least some non-human animal species, and on the other hand, that specifically human characteristics do exist, but from this fact does not follow that we should draw a sharp line between human and non-human animals. We reject the speciesist and segregationist perspective that establishes that only human beings possess a singular position in nature. Every animal species has its own characteristics and, therefore, there would be no place for a human exception, but there would be as many exceptions as animal species exist in the nature. Instead of the abyss established between human animals and non-human animals, we defend the perspective of the animal continuum, which allows recognizing the characteristics that we share with other animal species and, therefore, promotes the end of the speciesism.